Reconstruction of pediatric hand injuries caused by automatic cup-sealing machines in Taiwan. Issue 11 (November 2019) - Tsai, Yueh-Ju; Carvajal, Carolina Forero; Flores, Nicolas Moltedo; Lin, Tsan-Shiun; Yang, Johnson Chia-Shen; Chiang, Yuan-Cheng; Lin, Pao-Yuan
Objective: This study was performed to share our clinical experience and provide treatment strategies for pediatric hand injuries caused by automatic cup-sealing machines in Taiwan. Methods: Thirteen pediatric patients with an average age of 3.6 years were included in this retrospective study. Treatment was based on the location and depth of the injury and included full-thickness skin grafts, free or local flaps, and digital replantation. Some patients underwent contracture release during follow-up. Results: Thermal crush injuries affected the left hand in five patients and right hand in eight. Four patients with nine amputated fingers were treated by emergent digital replantation, four were treated by skin grafting, one was treated by nail bed repair, one underwent reconstruction with a local reversed dorsal digital and metacarpal island flap, one underwent reconstruction with a fascia graft for extensor tendon repair and pedicled groin flap coverage, and two underwent reconstruction with free anterolateral thigh fasciocutaneous flaps with a vascularized fascia lata graft for dorsal hand defects. All replanted fingers survived. Conclusion: Pediatric hand injuries, especially those caused by cup-sealing machines, can be devastating. Aggressive treatments including early reconstruction and rehabilitation should be performed for all pediatric hand injuries to achieve satisfactory functional restoration.